Sistem Pendukung Keputusan Pemilihan Marketing Officer Terbaik dengan Metode Weighted Aggregated Sum Product Assesment (WASPAS) (Studi Kasus: Bank BRI Unit Simpang Marendal) - Dewi Anggraini (Journal of Information System Research (JOSH), 2021)
PT. Bank Rakyat Indonesia (BRI) is one of the growing BUMN banks. Since its establishment BRI has played a role in advancing the nation and the State through its attention towards the development of small businesses, while continuing to run a modern banking business and be ready to compete. BRI's vision is "To become a Commercial Bank that always puts customer satisfaction first". While its mission includes: conducting the best banking activities by prioritizing services to micro, small and medium businesses to support the improvement of the community's economy, providing excellent service to customers through a wide spread network and supported by professional human resources by implementing good corporate practices governance.